Interaction of tumor necrosis factor-alpha and interferon-gamma with bronchial phagocytic cells in non-allergic bronchial asthma patients - A. B. Pirogov; A. G. Prihodko; N. A. Pirogova; Ju. M. Perelman (Сибирский научный медицинский журнал, 2024)
The contribution of immunoregulatory cytokines to the formation of cold airway hyperresponsiveness in asthma patients is important for understanding approaches to therapy. Aim of the study was to investigate the interaction of tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) with bronchial phagocytes in non-allergic asthma patients depending on the airway response to cold air. Material and methods. In 41 patients with asthma, standard monitoring of clinical symptoms of the disease was performed with assessment of the level of asthma control using the Asthma Control Test (ACT) questionnaire, basic spirometry, collection of induced and spontaneously produced sputum, as well as exhaled breath condensate (EBC), and a bronchoprovocation test of isocapnic hyperventilation with cold (–20 ºС) air (IHCA), the content of TNF-α, IFN-γ in EBC and cellular composition of sputum. Results. Cold airway hyperresponsiveness was revealed in 15 patients (group 1), and in 26 patients (group 2) bronchial reaction to IHCA was absent. There were no intergroup differences in the level of asthma control (17.1 ± 0.89 and 18.7 ± 0.63 ACT points, respectively; p > 0.05) and indices of lung function (FEV1 91.2 ± 4.07 and 98.8 ± 2.61 %, respectively; p > 0.05). In response to IHCA in sputum of group 1 patients, the number of neutrophils significantly increased, the number of macrophages, structurally integral epithelial cells decreased, proportionally to this, the level of IFN-γ increased significantly in EBC, TNF-α content did not change. Conclusions. The response to isocapnic hyperventilation with cold air in non-allergic asthma patients with cold airway hyperresponsiveness is characterized by an increase in the level of IFN-γ in the exhaled breath condensate with no significant changes in the content of TNF-α. The increase in the proportion of neutrophils in sputum under the influence of cold stimulus is accompanied by a decrease in the number of macrophages and structurally integral epithelial cells because of inflammatory damage, destruction and cytolysis.